Incidentally Discovered Bilateral Recurrent Laryngeal Nerve Injury Following Total Thyroidectomy: A Case Report and the Review of Literature - Seada Almutrafi; Talal A. Alsharari; Farah K. Alturki (Dr. Sulaiman Al Habib Medical Journal)
Recurrent laryngeal nerve (RLN) palsy is a well-known complication following thyroidectomy. When bilateral RLN palsy occurs, the immediate concern for surgeons is typically securing the airway, often through tracheostomy. However, we present a unique and intriguing case of bilateral adductor palsy following total thyroidectomy. A 55-year-old female with a history of gout presented with a progressively enlarging, painless neck mass over the past year, accompanied by breathing and swallowing difficulties, but without systemic symptoms such as weight loss or voice changes. Laboratory evaluations revealed normal thyroid function. Following ultrasound and fine needle aspiration findings, she underwent a total thyroidectomy. Postoperatively, the patient experienced a complication of bilateral vocal cord paralysis, resulting in airway compromise. This case serves as a reminder that, in some instances, the surgeon may not be at fault and that other subtle factors should be carefully considered in the diagnosis and management of such complications.